Analysis of the Trend of Using Persuasive Language in Abbreviations of Couple Names for Political Branding in the Election of Regent and Deputy Regent Candidates in Indonesia in 2024: A Netnography Study - Sudi, Mohamad; Sjoraida, Diah Fatma; Zulham; Khasanah, Umul; Bachtiar, Alfan (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study analyzes the use of persuasive language in candidate pair name abbreviations as a political branding strategy in the 2024 regent and deputy regent elections in Indonesia. A netnographic approach was employed to examine digital interactions on social media, online news platforms, and campaign platforms, with data collected from January to November 2024. Thematic analysis was conducted to identify linguistic patterns, socio-cultural relevance, and public responses to candidate pair name abbreviations. The results indicate that elements of persuasive language, such as alliterations, acronyms, and metaphors, often create abbreviations that are memorable and emotionally resonant. Local social and cultural contexts also play a significant role, with candidate pairs adapting symbols or terms specific to their regions to gain voter sympathy. Public responses to these abbreviations vary depending on their relevance and appeal, with creative abbreviations generally receiving more positive interactions on social media. Consistent digital strategies, such as hashtags and interactive visual content, further enhance the effectiveness of political branding for candidate pairs. This research provides new insights into political communication in the digital era, particularly in the context of regional elections. The findings underscore the importance of integrating linguistic, social, and digital elements in building a compelling political image. Additionally, the study contributes to the literature on persuasive language and political branding while offering practical guidance for campaign teams in designing innovative communication strategies.